Arthrospira platensis enriched with Cr(III), Mg(II), and Mn(II) ions improves insulin sensitivity and reduces systemic inflammation in equine metabolic affected horses - Tomal, Artur; Szłapka-Kosarzewska, Jolanta; Mironiuk, Małgorzata; Michalak, Izabela; Marycz, Krzysztof (Frontiers in Endocrinology, 2024)
Equine Metabolic Syndrome (EMS) is a critical endocrine condition in horses, characterized by hyperinsulinemia, hyperlipidemia, and insulin resistance, posing a significant threat to their health. This study investigates the efficacy of supplementing EMS-affected horses with Arthrospira platensis enriched with Cr(III), Mg(II), and Mn(II) ions using biosorption process in improving insulin sensitivity, glucose tolerance, reducing inflammation, and mitigating obesity-related fat accumulation. Our results demonstrate that Arthrospira supplementation reduces baseline insulin and glucose levels, contributing to decreased adipose tissue inflammation. Furthermore, Arthrospira supplementation results in a decrease in body weight and improvements in overall body condition scores and cresty neck scores. Additionally, administration of Arthrospira leads to reduced levels of triglycerides and aspartate aminotransferase, indicating a decrease in hepatic adiposity and inflammation. These findings suggest that Arthrospira, enriched with essential micro-and macroelements, can be an advanced feed additive to enhance insulin sensitivity, promote weight reduction, and alleviate inflammatory processes, thereby improving the overall condition of horses affected by EMS. The use of Arthrospira as a feed additive has the potential to complement conventional management strategies for EMS.